Knowledge, attitudes and practice about sanitation and hygiene: a midline evaluation in WASH areas of BRAC - Sifat-E-Rabbi; Ali, ARM Mehrab (BRAC Research and Evaluation Division (RED), 2019)
This study aimed to evaluate the impact of BRAC WASH (Water, Sanitation and Hygiene) programme on hygiene knowledge and practice of the people in intervention areas compared to baseline status. A population-based cross-sectional study with a pre-test and post-test design was conducted in 50 sub-districts of rural Bangladesh where BRAC WASH programme exists. A two-stage systematic sampling design was followed in drawing the sample. Data collection took place during November 2006- June 2007 at baseline and April-June 2009 at midline using a pre-tested structured questionnaire and physical verification. Findings reveal that knowledge and practice of hand washing at critical times (such as after contact with feaces and waste, before eating, cooking and serving food) significantly increased at midline compared to baseline. Knowledge about water contamination and water-borne diseases, water purification procedure, sanitation hygiene, rules of maintaining good health, and waste disposal at fixed place increased at midline. Availability of slippers, soap and water nearby latrine increased in intervention areas. However, there still exists room for improvement because practice of hygiene behaviour was not universal although they had knowledge of its importance. To achieve the targets of Millennium Development Goal, the WASH programme needs to pay more attention in providing knowledge related to personal hygiene.